2013
DOI: 10.18227/1982-8470ragro.v7i2.948
|View full text |Cite
|
Sign up to set email alerts
|

Gessagem na cultura da soja no sistema de plantio direto com e sem adubação potássica.

Abstract: Resumo -O gesso agrícola pode ser utilizado como fonte de enxofre, desta forma, melhorando a nutrição e promovendo ganhos na produtividade da cultura da soja em sistema de plantio direto. Objetivou-se com este trabalho avaliar os efeitos do enxofre (S) aplicados na forma de gesso agrícola na cultura da soja em sistema de plantio direto com e sem adubação potássica. O experimento foi conduzido no município de Guairá-SP em solo da classe LATOSSOLO VERMELHO Eutrófico. O delineamento experimental utilizado foi o d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
1
5
0
3
Order By: Relevance
“…Similar results were found in studies by Caires et al (1999), Neis et al (2010), Caires, Joris and Churka (2011), Rampim et al (2011), Moda et al (2013), and Pauletti et al (2014). Interaction between gypsum and phosphorous was not observed in the macro and micronutrients contents for the corn crop (Table 5).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Similar results were found in studies by Caires et al (1999), Neis et al (2010), Caires, Joris and Churka (2011), Rampim et al (2011), Moda et al (2013), and Pauletti et al (2014). Interaction between gypsum and phosphorous was not observed in the macro and micronutrients contents for the corn crop (Table 5).…”
Section: Resultssupporting
confidence: 88%
“…However, increases in corn yield by using gypsum without water deficit were observed in studies by and Zandoná et al (2015). Nevertheless, several studies did not indicate responses to gypsum applied in soybeans (CAIRES et al, 1998;2003;NEIS et al, 2010;RAMPIM et al, 2011;MODA et al, 2013).…”
Section: Introductionmentioning
confidence: 96%
“…4 Mg ha -1 (Figure 2A). This may be associated with the uptake of sulfur because this element plays an important role in crop nutrition as a constituent of essential amino acids (cysteine and methionine) and of several coenzymes (MODA et al, 2013). Sulfur deficiency impairs protein synthesis and causes a reduction in yield (EPSTEIN; BLOOM, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Our results showed no relationship between the S content of leaf tissue and the relative grain yield of five different crops spanning 31 crop harvests (Figure 7). Some authors found that S in leaf tissue increased with S application to soil; however, this effect resulted in no increase in grain yield (Rheinheimer et al, 2005;Frandoloso et al, 2010;Moda et al, 2013). Therefore, using leaf tissue analysis alone to guide S application requires caution because annual crops tend to take up nutrients in amounts exceeding their basic nutritional requirements (luxury consumption) (Ercoli et al, 2011).…”
Section: Sulfur Content Of Leaf Tissue and Grain Yieldmentioning
confidence: 99%